The Principle of Fairness, Political Duties, and the Benefits Proviso Mistake - Koltonski, Daniel (Journal of moral philosophy, 2016)
Recent debate in the literature on political obligation about the principle of fairness rests on a mistake. Despite the widespread assumption to the contrary, a person can have a duty of fairness to share in the burdens of sustaining some cooperative scheme even though that scheme does not represent a net benefit to her. Recognizing this mistake allows for a resolution of the stalemate between those who argue that the mere receipt of some public good from a scheme can generate a duty of fairness and those who argue that only some voluntary action of consent or acceptance of the good can generate such a duty. I defend a version of the principle of fairness that holds that it is the person’s reliance on a scheme for the provision of some product or service that generates duties of fairness to share in the burdens of sustaining the scheme. And, on this version, the principle of fairness is politically significant: regardless of whether the citizen has a duty to obey the law, she will still have important political duties of fairness generated by her reliance on the various public goods provided by those society-wide cooperative schemes sustained by the sacrifices of her fellow citizens.